Vanillic acid alleviates palmitic acid‐induced oxidative stress in human umbilical vein endothelial cells via Adenosine Monophosphate‐Activated Protein Kinase signaling pathway. Issue 7 (8th May 2019) - Ma, Wen‐Fang; Duan, Xu‐Chang; Han, Lin; Zhang, Ling‐Ling; Meng, Xue‐Mei; Li, Yun‐Long; Wang, Min
Abstract: Vanillic acid (VA), one of the phenolic acids metabolized by anthocyanidins, can modulate vascular reactivity by reducing the superoxide. We investigated that VA alleviated fatty acid‐induced oxidative stress and clarified its potential mechanisms in human umbilical vein endothelial cells (HUVECs). Our results showed that VA reduced the production of reactive oxygen species and malondialdehyde levels. It also restored mitochondrial membrane potential and enhanced the activities of antioxidant enzymes. In addition, VA promoted the expression of p‐Nrf2 and HO‐1 through LKB1/AMPK signaling pathway, as well as the level of SIRT1 and PGC‐1α. Moreover, compound C reduced the effect of VA on the enhancement of p‐Nrf2 and HO‐1. These results indicated that AMPK was an important target molecule of VA in the process of alleviating oxidative stress in HUVECs, providing a new potential evidence for vascular protection of anthocyanin in vitro. Practical applications: As a phenolic derivative and phase II metabolite of anthocyanins in vivo, VA can be found in various edible plants and fruits. This study revealed that VA improved oxidative stress in endothelial cells stimulated by palmitic acid by activating AMPK and its downstream proteins. VA could be a potential functional material for the protection of diabetic vascular complications. Abstract : AMPK is an important target molecule for vanillic acid to alleviate palmitic acid‐induced oxidative stress in HUVECs. Vanillic acid activates the AMPK‐Nrf2 signaling pathway and exerts a protective effect on mitochondrial function in HUVECs.